2012
DOI: 10.1038/gene.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput antibody sequencing reveals genetic evidence of global regulation of the naïve and memory repertoires that extends across individuals

Abstract: Vast diversity in the antibody repertoire is a key component of the adaptive immune response. This diversity is generated centrally through the assembly of variable, diversity and joining gene segments, and peripherally by somatic hypermutation and class-switch recombination. The peripheral diversification process is thought to only occur in response to antigenic stimulus, producing antigenselected memory B cells. Surprisingly, analyses of the variable, diversity and joining gene segments have revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
59
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 24 publications
12
59
3
Order By: Relevance
“…High-throughput Ab sequencing of naive versus IgM memory versus IgG memory repertoires revealed that IGHV3-30 and IGHV3-23 are the most commonly used heavy variable genes, both of which are dominant in the S. pneumoniae 23F human Ab response (10,48). Interestingly, IGHJ4 usage increased in memory subsets, and those containing IGHJ4 paired with IGHV3-30 found increased usage of IGHD3 family members, the same combination used in KE5.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput Ab sequencing of naive versus IgM memory versus IgG memory repertoires revealed that IGHV3-30 and IGHV3-23 are the most commonly used heavy variable genes, both of which are dominant in the S. pneumoniae 23F human Ab response (10,48). Interestingly, IGHJ4 usage increased in memory subsets, and those containing IGHJ4 paired with IGHV3-30 found increased usage of IGHD3 family members, the same combination used in KE5.…”
Section: Discussionmentioning
confidence: 99%
“…Selective antigenic pressures underlying the emergence of stereotyped gene rearrangements have been proposed both in zebra fish and humans (46,47). Furthermore, stereotyped B cell receptors (BCRs) are frequent in clones from different patients with chronic lymphocytic leukemia (CLL) (30,48,49) and also mantle cell lymphoma (MCL) (34) and splenic marginal zone lymphoma (SMZL) (32,50), suggesting stimulation/ selection by common antigens during lymphomagenesis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, antigen experience has been reported to result in decreased length and hydrophobicity of the heavy-chain third complementarity-determining region (CDR-H3) and to alter CDR-H3 amino acid content relative to the naive repertoire (8,9). Analysis of the VH repertoire in identical twins provided evidence that germline gene use is genetically predetermined (10), but other studies demonstrated that VH gene use for a particular B-cell subset among different donors is more closely related than are different B-cell subsets within an individual (8,9,11). However, because of technical limitations (13), these and other studies were confined to analysis of the heavy and light chain repertoires separately.…”
mentioning
confidence: 99%
“…Specifically, additional information is needed regarding how a history of pathogen and environmental exposure modulates the sequence and conformational properties of naive antibodies to yield a mature antibody repertoire that confers effective protection. High-throughput DNA sequencing of the heavy-chain variable (VH) gene repertoire from human donors has begun to delineate repertoire-wide differences among antibodies encoded by different B-cell subsets (8)(9)(10)(11)(12)(13)(14). For example, antigen experience has been reported to result in decreased length and hydrophobicity of the heavy-chain third complementarity-determining region (CDR-H3) and to alter CDR-H3 amino acid content relative to the naive repertoire (8, 9).…”
mentioning
confidence: 99%